Towards an understanding of the caring phenomenon - why is it so topical? : a search for its role and its attributes in holistic education - Bhaur, Muhammad (2016)
Traditional liberal education has provided one-size-fits-all schooling, followed by neoliberal policies in the past 30 years, resulting in losing the purpose of education to build well-rounded personalities and to ensure quality education for all. Instead, the ideal today is the homo economicus able to further personal goals on self-interest, and the global divide between the haves and have-nots has increased. The research problem rises from the alternative view to the purpose of education, to fostering the learner’s full human growth, and focuses on holistic education as expressed in the ethics of care theory of Nel Noddings and my life experiences in four diverse learning cultures. Meta-analysis and auto-ethnography were used as research methods. Noddings’ work on the care phenomenon was studied with meta-analysis. Auto-ethnography based on my educational experiences from four different cultures was employed to spot the holistic education interrelationships with the care theory of Noddings. Noddings’ themes of care are interwoven into holistic education via inquiry, dialogue, response and reflection. These and the auto-ethnographic data correspond with the conceptual framework of holistic education created from relevant theory in the study, connecting the physical, intellectual, emotional, social, creative, and spiritual, into interconnectedness and self-actualization. The author’s voice lends insightful support to Noddings’ propositions of care into the development of a holistic individual, emphasizing equality, purposefulness and meaning of education.